2016
DOI: 10.1149/2.0841608jes
|View full text |Cite
|
Sign up to set email alerts
|

High Quality MoSe2Nanospheres with Superior Electrochemical Properties for Sodium Batteries

Abstract: Highly ordered MoSe 2 nanospheres are successfully fabricated via a facile colloidal route. The unique as-obtained MoSe 2 nanospheres render the high-rate transporation of sodium ion due to small size and high specific surface area. As the anode, MoSe 2 nanospheres yield the initial discharge/charge capacities of 520/430 mAh g −1 for potentials ranging from 0.1 to 3 V at a current rate of 0.1 C with an 80% capacity retention over 200 cycles. In addition, MoSe 2 nanospheres also demonstrate excellent electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 52 publications
3
30
1
Order By: Relevance
“…These two peaks are ascribed to the insertion of sodium ions into the interlayers of MoSe 2 forming Na x MoSe 2 ; and conversion of Na x MoSe 2 to Mo and Na 2 Se with the formation of a solid electrolyte interphase (SEI) film, respectively . In the anodic scanning of the first cycle, the peak at 1.8 V is attributed to the oxidation of Na 2 Se to Se rather than MoSe 2 . As a result, from the second cathodic sweeping, the peak emerging at 1.4 V is corresponding to the conversion reaction from Se to Na 2 Se which is the reason for the peaks difference between the first cathodic scanning and subsequent reduction process.…”
Section: Resultsmentioning
confidence: 96%
“…These two peaks are ascribed to the insertion of sodium ions into the interlayers of MoSe 2 forming Na x MoSe 2 ; and conversion of Na x MoSe 2 to Mo and Na 2 Se with the formation of a solid electrolyte interphase (SEI) film, respectively . In the anodic scanning of the first cycle, the peak at 1.8 V is attributed to the oxidation of Na 2 Se to Se rather than MoSe 2 . As a result, from the second cathodic sweeping, the peak emerging at 1.4 V is corresponding to the conversion reaction from Se to Na 2 Se which is the reason for the peaks difference between the first cathodic scanning and subsequent reduction process.…”
Section: Resultsmentioning
confidence: 96%
“…Each layer consists of a metal sandwiched between two chalcogen atoms in the form of X‐M‐X. The highly researched members of the family are the Group 6 dichalcogenides, namely MoS 2 , MoSe 2 and WS 2 , owing to their promising potential in many energy‐related applications, particularly for electrochemical hydrogen production, batteries and capacitors . [18–20] Additionally, these materials also offer technological advances in a broader spectrum of applications ranging from electronic, optoelectronic, spintronics, solar cells, sensors, biological, biomedical and even lubrication .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the MoSe 2 nanospheres could render the high sodium transport rate and also possessed desired electrochemical performance at high current densities. Based on first‐principles simulation, the activation barriers for sodium ion transportation on the surface and interlayer of the MoSe 2 are 0.344 eV and 1.31 eV respectively, indicating the good application of MoSe 2 nanospheres for anode materials of Na ion batteries . Furthermore, in order to achieve synergetic effects, hybridization composites based on 0D TMDs were considered.…”
Section: Applicationsmentioning
confidence: 99%